Identifikasi Molekular Bakteri Glukanolitik Indigenous KE-B6 dari Saluran Pencernaan Bekicot (Achatina fulica) - Wijanarka Wijanarka; Sri Pujiyanto; Budi Raharjo (Jurnal Biologi Papua, 2019)
Glucanolitic bacteria are bacteria that have the ability to break down glucan into glucose monomer units. The ability of the bacteria is caused by the presence of glucanase enzymes. The choice of glucanase derived from bacteria is based on the ability and speed of bacterial growth in terms of producing glucanase enzymes. The presence of bacteria and protozoa in the digestive tract symbiotic with each other to digest cellulose or concomitant materials . Based on the ability of the way of life to digest forage and leaf litter, it is suspected that snails (Achatina fulica) have the ability to produce glucanase biocatalysts, especially in the digestive tract. To find out the characteristics and characteristics of indigenous bacteria snail canals, identification of KE-B6 bacteria is carried out molecularly so that accurate and accurate results are obtained. The Basic Alignment Search Tools BLAST results of KE-B6 bacterial isolates based on 16S rDNA sequence data with 27F (Forward) and 1492R (Reverse) primers showed that these bacterial isolates had homology of 99.64% to Serratia marcescens.  Key words: bacteria, glucanolitic, A. fulica, Serratia marcescens.